The model of energy distribution during electron beam input in welding process. Issue 4 (November 2020) - Kurashkin, S O; Tynchenko, V S; Seregin, Yu N; Murygin, A V; Kukartsev, V V; Tynchenko, V V
Abstract: Modeling is one of the most important parts of applied research, the processes for which carrying out full-scale experiments is either expensive or highly labor-intensive. The article deals with the problem of modeling the energy distribution at the stage of electron beam input during welding. The solution to this problem will allow not only to reduce the cost of testing the technological parameters of electron beam welding of products with new geometry or from new materials, but also to support the decision-making of the technologist when optimizing the manufacturing process of existing products. Based on the theory of thermal processes, mathematical models have been developed that consider the characteristics of the materials to be welded and the technological parameters of the electron-beam welding process. In the course of experimental studies, the energy distribution was simulated when the electron beam was introduced for structures made of two different materials with different geometries. The obtained models for calculating the temperature at the input section not only supplement the complex of existing mathematical models of the electron beam welding process, but also allow expanding their application for calculating and optimizing the welding process, taking into account the excess temperature at the electron beam input section. In the future, this will allow considering the temperature spread at the input stage and obtaining a more stable quality of the welded seam with fewer root defects.